Comparison of the Quality of Life of Regular Hemodialysis Patients Based on the World Health Organization-BREF Score with the Missoula Score at RSUD Dr. Soegiri Lamongan - Eka Ari Puspita; Muhammad Rafi Zufar Priyambodo; Sri Widyaningsih; Eko Budi Santoso (OJS Universitas Muhammadiyah Gresik, 2025)
Abstract: Background: Chronic kidney disease is becoming a health problem worldwide. The fact that chronic kidney disease patients cannot be separated from hemodialysis throughout their lives causes a significant decrease in physical and cognitive abilities in kidney failure patients, so that assessment of regular hemodialysis patients is very important because it can affect optimal quality of life. Objective: To determine the comparison of quality of life of regular hemodialysis patients based on the World Health Organization Quality of Life-BREF score with the Missoula VITAS Quality of Life Index-15 score. Methods: This study uses an observational analytical method, with a cross sectional study to be conducted on regular hemodialysis patients caused by chronic kidney disease at Dr. Soegiri Lamongan Hospital. The instruments used are the WHOQOL-BREF quality of life scale and the Missoula score. Discussion: The results of this study showed that there were significant differences in several quality of life domains between WHOQOL-BREF and Missoula score. WHOQOL-BREF tends to score higher in the physical and environmental health domains. In contrast, MVQOLI provides a more in-depth assessment of aspects of symptoms and physical function as well as psychological well-being. Conclusions: There was a difference in quality of life in patients on regular hemodialysis therapy with World Health Organization-BREF and Missoula scores.